2015
DOI: 10.3390/molecules200611272
|View full text |Cite
|
Sign up to set email alerts
|

Selected Compounds Structurally Related to Acyclic Sesquiterpenoids and Their Antibacterial and Cytotoxic Activity

Abstract: By implementing a common and industrially used method, 30 compounds which are structurally related to geranyl acetone, nerolidol, farnesal, farnesol and farnesyl acetate were obtained. Their antimicrobial activity against Staphylococcus aureus, Enterococcus faecalis, Enterococcus faecium, Escherichia coli, Klebsiella pneumoniae and Acinetobacter baumannii bacteria was investigated. Pharmacophore models were proposed based on the obtained results and 3D QSAR modelling. Cytotoxic effects against mainly human imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…This peak identifies the compound Q which is farnesyl acetate which has the name 3,7,11trimethyl-1,6,10-dodecatrien-3-ol. This Q compound has biological activity as an antibacterial against S. aureus, E. faecalis, E. faecium, E. coli, K. pneumoniae and A. baumannii [11].…”
Section: Resultsmentioning
confidence: 99%
“…This peak identifies the compound Q which is farnesyl acetate which has the name 3,7,11trimethyl-1,6,10-dodecatrien-3-ol. This Q compound has biological activity as an antibacterial against S. aureus, E. faecalis, E. faecium, E. coli, K. pneumoniae and A. baumannii [11].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, Bonikowski et al studied the antibacterial and cytotoxic effects of 30 components which are structurally related to geranyl acetone, nerolidol, farnesal, farnesol, and farnesyl acetate were obtained. The authors stated that these components have negligible toxicity on various human cell lines and may have the potential to be used safely (Bonikowski et al, 2015). In another study, the effects of farnesol on HeLa human cervical cancer cells were investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Farnesol also exerts a growth inhibitory effect and increases the formation of reactive oxygen species (ROS) (Joo et al, 2015). On the other hand, authors stated that these components have negligible toxicity on various human cell lines and may have the potential to be used safely (Bonikowski et al, 2015). In another study, the effects of farnesol on HeLa human cervical cancer cells were investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings of antilymphoma activity of terpenes isolated from PEAm are consistent with previously published reports. Specifically, the authors of [ 44 ] found that sesquiterpene FA induced cytotoxicity against the HL-60 cell line [ 44 ]. In addition, researchers have found that Gg exhibits important chemopreventive and suppressive ac-tivities on cancer cell lines by arresting the cell cycle in the G1 phase and inducing the down-expression of cyclin D1 and induced apoptosis by activating caspases 8, 9, and 3 in cell lines DU145 and DLD1 [ 45 , 46 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%